Influence of Putrescine Application on Storability, Postharvest Quality and Antioxidant Activity of Two Iranian Apricot (Prunus armeniaca L.) Cultivars - Gholamhossein DAVARYNEJAD; Mehdi ZAREI; Elham ARDAKANI; Mohamad Ebrahim NASRABADI (Notulae Scientia Biologicae, 2013)
The limited postharvest storage life of apricot is the focus of this study. Presenting a solution to improve the postharvest storage of studied apricot cultivars is the goal. Studding the effect of different concentration of postharvest putrescine on quality attributes and antioxidant activity of two apricot cultivars during storage is the approach taken. The two apricot cultivars (‘Lasgerdi’ and ‘Shahrodi’) were harvested at the commercial ripening stage, and fruits were immerged in 1, 2, 3 and 4 mM putrescine as well as distilled water (control) for 5 min, then fruits were packed in boxes with polyethylene cover and stored at 4°C and 95% relative humidity for 20 days. The changes in weight loss, fruit firmness, total soluble solids, titratable acidity, pH, maturity index, ascorbic acid, total phenolics and antioxidant activity were estimated after 0, 5, 10, 15 and 20 days during storage. The results showed that the weight loss, total soluble solids, pH and maturity index increased significantly while the fruit firmness, titratable acidity, ascorbic acid, total phenolics and antioxidant activity decreased significantly during storage for both cultivars. During storage, a significant difference between control and putrescine treatments in all measured parameters is observed. The putrescine treatments reduced significantly the weight loss and maintained their firmness. In this condition, the highest and lowest of titratable acidity, ascorbic acid, total phenolics and antioxidant activity were observed in treatments of 4 mM putrescine and control, respectively. The data revealed that the quality of apricot fruits was improved by the use of putrescine treatment due to its effect on delaying the ripening processes.